Learner Support Systems in Distance Learning Education Systems (Comparative Analysis of VU and AIOU) - Attiq-ul-Rehman, Ahmad; Shahzadi, Amina (MO.RI Publishing, 2025)
This examine sightsees and equates the learner assist systems at Virtual University (VU) and Allama Iqbal Open University (AIOU) in Pakistan, focusing on their effectiveness in talking the desires of distance newbies. The number one independent is to evaluate how these structures differ in structure, delivery, and consumer-friendliness, and to assess their strengths and obstacles in facilitating pupil appointment, retention, and academic success. A mixed-strategies method is used, combining quantitative surveys, qualitative semi-based interviews, recognition organization discussions, and observations. Virtual Learning Management System (LMS), with over 85% of respondents indicating satisfaction with the availability of course materials. AIOU’s hybrid model obtained combined reviews, with 70% of college students knowing the significance of its nearby take a look at centers and conventional broadcast strategies in addressing technological gaps in rural areas. The findings monitor that VU’s completely digital version excels in scalability and correctness however faces demanding situations in terms of virtual inequality, with college students in rural and underserved areas suffering with internet access and restrained communique with teachers. AIOU’s hybrid model, combining conventional face-to-face help with virtual assets, is more inclusive, mainly for college students in faraway regions, but suffers from inconsistencies in useful resource allocation and logistical disorganizations. The take a look at highpoints the rank of addressing the digital divides and suggests that a hybrid method, integrating the strengths of both models, should higher meet the diverse needs of newbies. The research donates to the broader discourse on distance schooling in Pakistan and offers references for a hit learner guide structures to beautify scholar success and appointment. The study also opens avenues for future studies at the lengthy-time period impact of various learner help models and the way they may be tailor-made to cope with diverse pupil wishes crossways socio-economic and geographic contexts. This study provides essential new facts for the Application & improvement of learner help machine in Pakistan and different comparable international instances. It is likewise highlights how innovation distances mastering can enhance accessibility and inclusivity for all college students.